Fatigue life estimation of explosive cladded transition joints with the use of the spectral method for the case of a random sea state. (May 2020) - Böhm, Michał; Kowalski, Mateusz
Abstract: The problem with fatigue lifetime estimation of explosive cladded transition joints under random loading conditions has been described. The paper presents the fatigue test results performed for the random state of tension-compression under a generated spectrum according to the Pierson-Moskowitz model. The obtained spectrum has a non-Gaussian characteristic. The tested material consists out of a transition joint clad with four layers of aluminium alloy A5083, A1050, Titanium Grade 1 and steel Grade D. The material has been tested for the existence of residual stresses after the welding process with the hole drilling method. The welding process has been also simulated with ANSYS and the residual stresses have been generated for the Goldak volumetric distribution. The obtained values of residual stresses comprise to the values of real tests performed for the hole drilling method. The information about the residual stress values have been taken into account in the process of fatigue lifetime estimation in the form of non-zero mean stresses compensation inside the clad. The fatigue life has been calculated with the use of the frequency domain method. The Goodman mean stress compensation model has been used in the process of residual stress compensation. The non-gaussianity has been compensated with the use of the Bracessi formula. The obtained fatigue life assessment results have been compared with stand test results. The calculated results are within the scatter area of 3, but individual scatter values have been calculated for calculated series. Highlights: New fatigue test results under random sea states for explosive bonded transition joints. We discuss the general approach to perform fatigue assessment with the use of spectral method for transition joints. We discuss and perform the procedure of residual stress calculations and measurements for transition joints. We discuss methods to compensate the mean stress effect and non-Gaussian effect for these joints with the use of frequency defined method. We have performed a comparison of experimental and calculated fatigue lifetime results.